Implementation of Problem-Based Learning to Enhance Critical Thinking Skills in Junior High School Students - Abdullah, Oktosiyanti MT.; Syaharuddin, Syaharuddin; Husain, Husriani; Yasriuddin, Yasriuddin; Mendrofa, Netti Kariani (PT Inovasi Pratama Internasional, 2025)
This article investigates the implementation of Problem-Based Learning (PBL) as a pedagogical strategy to cultivate critical thinking skills among junior high school students. Utilizing a qualitative research design, the study synthesizes insights from recent research and theoretical frameworks published within the last five years, employing classroom observations, interviews, document analysis, and focus groups to gather comprehensive data. The analysis highlights PBL's effectiveness in fostering critical thinking through student-centered, inquiry-based learning processes, emphasizing improvements in analytical reasoning, problem-solving abilities, and collaborative communication. Key findings reveal that while PBL significantly enhances these skills, successful implementation is contingent upon addressing challenges related to teacher preparedness, time constraints, uneven student participation, and resource limitations. Strategies such as targeted professional development for teachers, structured scaffolding for students, and leveraging technology are discussed as potential solutions. The article concludes with recommendations for educators and policymakers, advocating for systemic changes to support widespread adoption of PBL and promote a shift towards more engaging, student-centered learning environments. This research contributes to the ongoing dialogue on innovative teaching practices that equip students with the essential skills needed for success in the 21st century.